2004
DOI: 10.2136/sssaj2004.8090
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Manure Effects on Soil and Aggregate‐Associated Carbon and Nitrogen

Abstract: In agricultural systems, maintenance of soil organic matter (SOM) has long been recognized as a strategy to reduce soil degradation. No‐tillage and manure amendments are management practices that can increase SOM content and improve soil aggregation. We investigated the effects of 10‐yr of different tillage systems and N sources on soil aggregate‐size distribution and aggregate‐associated C and N. The study was a split‐plot design replicated four times. The main plot treatment was tillage (no‐tillage, NT; conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
174
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(210 citation statements)
references
References 35 publications
33
174
2
1
Order By: Relevance
“…Previous studies have suggested that OC is more effectively protected and more stable in microaggregates, whereas macroaggregates provide a niche for the storage of labile C [3], [5], [10]. Fertilization, a common agricultural practice, has been found to significantly influence aggregate formation and OC distribution in aggregates [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that OC is more effectively protected and more stable in microaggregates, whereas macroaggregates provide a niche for the storage of labile C [3], [5], [10]. Fertilization, a common agricultural practice, has been found to significantly influence aggregate formation and OC distribution in aggregates [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…External organic amendments as well as increased fine root inputs provided more organic sources compared with the unfertilized treatment. Mikha and Rice (2004) reported that aggregate-protected labile C and N fractions were significantly greater for 0.25-to 2-mm aggregates in manure treatment than microaggregates (<0.25 mm) in chemical fertilization treatment and that 0.25-to 2-mm aggregates contribute more to relevant nutrient cycling. Mikha and Rice (2004) reported that aggregate-protected labile C and N fractions were significantly greater for 0.25-to 2-mm aggregates in manure treatment than microaggregates (<0.25 mm) in chemical fertilization treatment and that 0.25-to 2-mm aggregates contribute more to relevant nutrient cycling.…”
Section: Relationship Between Soil Aggregation and Associated Carbon mentioning
confidence: 99%
“…Maintaining high stability of soil aggregates is essential for improving crop productivity, preventing soil degradation, and minimizing environmental pollution (Mikha and Rice, 2004). Maintaining high stability of soil aggregates is essential for improving crop productivity, preventing soil degradation, and minimizing environmental pollution (Mikha and Rice, 2004).…”
mentioning
confidence: 99%
“…To evaluate soil mineralizable (active) forms of C and N, a short-term aerobic laboratory incubation was conducted for 28 days at 25 • C under a soil water content of −0.033 MPa [26,27]. The 8-mm sieved and air-dried soil was conditioned to a water content of 0.21 g H 2 O g −1 soil (approximately −0.033 MPa) by gradually adding an appropriate amount of deionized (DI) water before the incubation [28].…”
Section: Mineralizable (Active) Carbon and Nitrogen Fractionsmentioning
confidence: 99%
“…Mineralizable C was determined using the static sealed chamber method to evaluate CO 2 evolution for the 28-day incubated soil [26,27]. In short, 40 g of recently wetted soil (0.21 g H 2 O g −1 soil) associated with each treatment was added to a 170 mL specimen cup and placed in an approximately 1-L (the volume of each canning jar was measured precisely) wide mouth canning jar containing 20 mL of water.…”
Section: Mineralizable (Active) Carbon and Nitrogen Fractionsmentioning
confidence: 99%